In Vivo Efficacy of Telithromycin (HMR3647) against Streptococcus pneumoniae and Haemophilus influenzae - Okamoto, Hiroki (American Society for Microbiology, 2001)
The in vivo activity of telithromycin against erythromycin A- and penicillin G-resistant Streptococcus pneumoniae was superior to that of azithromycin, clarithromycin, cefdinir, and levofloxacin. In respiratory tract infections caused by erythromycin A-susceptible S. pneumoniae or Haemophilus influenzae in mice, telithromycin was more effective than clarithromycin and comparable to azithromycin.